Validitas Lembar Kerja Peserta Didik Berbasis Discovery Learning pada Submateri Klasifikasi Jamur di Kelas X SMA - Ahmad Aloy Saputra; Laili Fitri Yeni; Eko Sri Wahyuni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Discovery learning-based Student Worksheets are printed teaching materials containing materials and instructions for implementing learning tasks that can help students make discoveries in the learning process. This study aims to determine the feasibility of student worksheets based on discovery learning in the class X high school mushroom classification submaterial based on the results of an inventory of macrocosmic fungi in the Gunung Majau Protected Forest, Sambas Regency. The research instrument used is a validation sheet, which includes aspects of content, language, presentation and graphics. The method used in this research is a descriptive method with a quantitative research form. The results of this study indicate that the validation of student worksheets based on discovery learning was carried out by five validators with a CVI (Content Validity Index) value of 0.99 which was declared feasible or valid. Based on the results of the validation, it can be concluded that the student worksheets based on discovery learning from the inventory of macrocosmic fungi in the Gunung Majau Protection Forest, Sambas Regency are feasible in terms of content with a CVI value of 0.99 (feasible or valid), so they can be used as teaching materials in the classification sub-material class X high school mushrooms.